PEDAGOGICAL CONDITIONS FOR FORMING COMMUNICATIVE COMPETENCE IN STUDENTS - Irgashova M. A. (Galaxy International Interdisciplinary Research Journal, 2024)
The article reveals the pedagogical conditions for the formation of communicative competence among students.